Pengembangan Sistem Penilaian Berbasis Certainty Factor dalam Pedidikan Berbasis Ketarunaan - Brama Kurniawan; Masduki Zakaridjah (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2025)
This study aims to develop a character assessment system for students in cadet-based education using the Certainty Factor (CF) method. The research employed the Research and Development (R&D) approach following the Borg & Gall model, which consists of ten stages. The assessment instruments were designed based on guidelines from the Directorate General of Vocational Education, academic journals, and references from the Indonesian National Armed Forces. The trial subjects included cadet instructors, cadet commanders, student affairs staff, and homeroom teachers at SMKN 3 Yogyakarta. Data collection techniques included interviews, observations, and questionnaires, which were analyzed quantitatively. The results show that the developed system has a high level of accuracy and supports objective and efficient character evaluation. User feasibility scores indicate 85% for Usefulness, 82% for Ease of Use, 84% for Ease of Learning, and 86% for Satisfaction. The system is considered highly feasible for implementation in cadet-based education and is recommended for further development.